Primary care diagnosis of gastroschisis: case report - Md Nor, Mohd Zamir; Said, Abdul Hadi; Che Yusof, Mohd Daud (Academy of Family Physicians of Malaysia, 2023)
Introduction: Gastroschisis is a congenital abdominal wall defect occurring in approximately 5 in 10,000 live births. Prolonged amniotic fluid exposure can impair mesenteric blood flow and irritate the foetal intestinal wall. This case study shared an early gastroschisis detection by primary care providers. Case presentation: A 23-year-old Malay gravida 2 Para 1 made a booking at 12 weeks’ gestation. During a 28-week antenatal ultrasound, the foetal abdominal circumference was at 26 weeks, and there was presence of gastroschisis (herniated and thicker bowel (18.5 mm) loops oating freely in the amniotic uid. e patient was referred to the Obstetrics & Gynecology (O&G) team and seen at 30 weeks. e patient was counselled on the risks of intrauterine mortality, chromosomal abnormality, early neonatal death, and preterm in this pregnancy. e patient experienced preterm premature rupture of the membranes (PPROM) at 35/40+6/7 weeks' gestation. e baby was admitted to the intensive care unit (NICU), and the pediatric surgical team made successful delayed primary closure and viscera reduction surgery. Discussion: Even though gastroschisis can be identied as early as 12 weeks of gestation, the prenatal imaging characteristics of gastroschisis can be challenging. In this case, the pathology was not detected before 28 weeks of gestation, despite three ultrasounds performed from 12 – 26 weeks. e pathology was eventually detected at 28 weeks’ gestation, and she was referred promptly, bringing a good prognosis for the neonates. Conclusion: Early gastroschisis diagnosis at the primary care level is vital as this problem requires prompt referral to tertiary centres to improve the neonate’s prognosis.